Six new species of Chelipoda (Diptera: Empididae) from Shennongjia, China - Zhang, Leyou; Lin, Chen; Gao, Shang; Yang, Ding (Zootaxa, 2024)
Only three species of Chelipoda were known to occur in Shennongjia National Nature Reserve. The following six species are described as new to science: C. biancistroides sp. nov., C. conica sp. nov., C. curva sp. nov., C. digitiformis sp. nov., C. dorsispina sp. nov. and C. trifurcata sp. nov. A key to separate these species is presented.